New mechanism of a daylighting system using optical-fiber-less design for illumination in multi-storey building. (1st September 2021) - Vu, Duc Tu; Vu, Hoang; Shin, Seoyong; Tien, Tran Quoc; Vu, Ngoc Hai
Highlights: A fully new scheme of the daylighting using optical-fiber-less design and hybrid system. Aiming to guide light deeply and efficiently for a given multi-storey building. The optical efficiency and energy saving can reach 63.7 % and 46.5%, respectively. Abstract: In this study, the fully new scheme of the daylighting system is devised and a few avenues are proposed toward large scale illumination area with the highly efficient luminous flux and modest cost. Rather than a previously common design, consisting of a sole system, we work out two subsystems for a generic daylighting system: outdoor and indoor subsystems. For the outdoor subsystem, aiming to guide light deeply and efficiently for a given multi-storey building, we first capitalize on a simple design of two mirrors to collect the sunlight and transport it in free-space, which negligibly penalizes the optical loss. To guide light to each particular area inside building, we further propose two options for the indoor subsystem taking into consideration between cost and performance: first with the Fresnel lens + circular plastic optical fiber (POF) bundle and second with the waveguide concentrator + flat POF bundle. The quantitative assessment unravels that the optical efficiency of the latter is higher than that of the former, 63.7 % vs 48.7 %. Still, the real implementation of the Fresnel lens + circular POF is more prone and we indeed demonstrate a principle-of-concept system. Such design also preferably implements with a LED panel, in an embodiment of a so-called hybrid daylighting system, to grant light in overcast and night-time situations. This proposed daylighting system also enables exceptional merit in calculated energy saving, up to roughly 46.5% in a year with sunlight condition as in Ho Chi Minh City (Vietnam), as electrical light is used properly and barely. All things taken into account, this approach indicates a likely perspective for fostering a new generation of the daylighting system that making use of sparingly optical fiber.